2015
DOI: 10.1590/s0100-204x2015000400007
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi in soil aggregates from fields of "murundus" converted to agriculture

Abstract: -The objective of this work was to evaluate the spore density and diversity of arbuscular mycorrhizal fungi (AMF) in soil aggregates from fields of "murundus" (large mounds of soil) in areas converted and not converted to agriculture. The experiment was conducted in a completely randomized design with five replicates, in a 5x3 factorial arrangement: five areas and three aggregate classes (macro-, meso-, and microaggregates). The evaluated variables were: spore density and diversity of AMF, total glomalin, tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…AMF species from Order Diversisporales (genus Acaulospora), and Gigasporales (genus Dentiscutata, Gigaspora, and Scutellospora) are common in semi-arid sites (Dandan & Zhiwei 2007;Silva et al 2014), and in acid soil with low phosphorous availability (Ramos et al 2008). However, disturbances and changes in soil properties, such as soil pH, total organic carbon and available phosphorous can be favorable for Glomerales species (Oehl et al 2010;Jansa et al 2014;Carneiro et al 2015). Therefore, changes in soil properties induced by the invasive plant may contribute to constrain the occurrence of some AMF species, reduce AMF sporulation, and decrease AMF diversity and AMF dominance (Tab.…”
Section: Discussionmentioning
confidence: 99%
“…AMF species from Order Diversisporales (genus Acaulospora), and Gigasporales (genus Dentiscutata, Gigaspora, and Scutellospora) are common in semi-arid sites (Dandan & Zhiwei 2007;Silva et al 2014), and in acid soil with low phosphorous availability (Ramos et al 2008). However, disturbances and changes in soil properties, such as soil pH, total organic carbon and available phosphorous can be favorable for Glomerales species (Oehl et al 2010;Jansa et al 2014;Carneiro et al 2015). Therefore, changes in soil properties induced by the invasive plant may contribute to constrain the occurrence of some AMF species, reduce AMF sporulation, and decrease AMF diversity and AMF dominance (Tab.…”
Section: Discussionmentioning
confidence: 99%
“…Due to expansion and consolidation of agricultural frontiers, the original vegetation of the Cerrado was reduced by almost half in the country (IBGE 2010). Information on the effect of distinct agricultural management practices and land uses upon AMF populations in the Cerrado are scarce (Cordeiro et al 2005;Miranda et al 2005;Ferreira et al 2012;Assis et al 2014;Carneiro et al 2015), and occurrence of AMF species in this biome has been reported in few studies. Siqueira et al (1989) found 19 AMF species associated with native (woody and grassy) plants of Cerrado, indicating that Acaulospora morrowiae, Acaulospora scrobiculata, Cetraspora pellucida, and Gigaspora sp.…”
Section: Introductionmentioning
confidence: 99%
“…These findings support our hypothesis that EXO soils have lower AMF diversity than NAT soils. Several studies (e.g., Richardson et al 2000;Hawkes et al 2006;Rodríguez-Echeverría et al 2009;Oehl et al 2010;Carneiro et al 2015;Souza et al 2016b) also showed a lower AMF diversity in disturbed soils by biological invasion of invasive exotic species (e.g., A. senegal, A. seyal, A. albida, E. albensis, Olpidium spp., Cryptostegia madagascariensis, Sesbania virgata, P. juliflora, and Parkinsonia aculeata) in comparison with soil in natural conditions. These results are in agreement with previous studies (Soumare et al 2015;Ayanu et al 2015;Zubek et al 2016;Callaway et al 2008;Tanner and Gange 2013) and support our hypothesis that invasive plants are associated with specific AMF species.…”
Section: Discussionmentioning
confidence: 94%
“…First, P. juliflora usually form large monospecific plant populations, as was the case in our study, thus reducing the diversity of host-plants available to the AMF community. Consequently, this changes soil organic carbon inputs (Andrade et al 2009;Dandan and Zhiwei 2007;Oehl et al 2010;Jansa et al 2014;Silva et al 2014;Carneiro et al 2015;Sousa et al 2011;Souza et al 2016a) and decreases AMF's growth and proliferation in the absence of a diverse mycorrhizal plant community (Zubek et al 2013). Secondary metabolites produced by P. juliflora negatively affect native plants growth by disrupting their mutualistic associations with the unaltered AMF community (Andrade et al 2009;Zubek et al 2013).…”
Section: Discussionmentioning
confidence: 99%